2007
DOI: 10.1016/j.brainres.2006.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Different activation patterns for working memory load and visual attention load

Abstract: Attention is a basic component of cognitition, and is modulated by cognitive load. We aimed to map the common network that supports attentional load across different tasks using functional magnetic resonance imaging (fMRI). Twenty-two healthy volunteers performed two sets of tasks with graded levels of cognitive load: verbal working memory (WM) and visual attention (VA) tasks. For both tasks, increased cognitive load (WM-load and VA-load) activated a common network comprising parietal and occipital cortices, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 57 publications
11
101
0
Order By: Relevance
“…Inspection of significant activity revealed an extensive network of regions, including bilateral superior parietal lobe (BA 7), right occipital lobe (BA 18), bilateral cerebellar regions and right middle frontal lobe (BA 6), consistent with the distribution of brain regions responsive to visual WM load reported in previous studies [19,20,24,25], specifically those regions that typically show increased positive load-related responses. Regions such as the bilateral parietal cortex, medial parietal cortex, cingulate and medial frontal cortex that typically demonstrate negative load-related responses in young adults [46,63,64] were not observed, independent of group. A significant group × load interaction was observed in the right anterior cingulate (AC) for the encoding phase, but not for maintenance or retrieval.…”
Section: Resultsmentioning
confidence: 99%
“…Inspection of significant activity revealed an extensive network of regions, including bilateral superior parietal lobe (BA 7), right occipital lobe (BA 18), bilateral cerebellar regions and right middle frontal lobe (BA 6), consistent with the distribution of brain regions responsive to visual WM load reported in previous studies [19,20,24,25], specifically those regions that typically show increased positive load-related responses. Regions such as the bilateral parietal cortex, medial parietal cortex, cingulate and medial frontal cortex that typically demonstrate negative load-related responses in young adults [46,63,64] were not observed, independent of group. A significant group × load interaction was observed in the right anterior cingulate (AC) for the encoding phase, but not for maintenance or retrieval.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the number of items in a display, for example, also increases attentional load. Indeed, an fMRI study by Tomasi et al (2007) found that parietal cortex was driven both by cognitive load in an attention and memory task, whereas PFC was loaddriven only in the WM task. This may indicate that PFC is more specifically related to WM-an assumption also supported by the existing computational models of WM (Gruber et al, 2006;Hazy et al, 2006;O'Reilly and Frank, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Brünken et al (2003) have provided helpful guidance for researchers who would like to use measures that are more direct, objective, and valid than measures typically used to this point in CLT investigations. Brünken and his colleagues note the potential for neuroimaging techniques (see Tomasi et al 2007 for a recent example) when it becomes more practical and better understood, but for the present they highlighted the benefits of the dual-task paradigm that is well known among working memory researchers. Essentially, dual task approaches involve using two tasks where one of the two tasks (e.g.…”
Section: Cognitive Load Theory and Fdimentioning
confidence: 94%